DIAGNOSTIC AND PROGNOSTIC VALUE OF THE IMMUNE RESPONSE RATES FOR GROUP A STREPTOCOCCUS ANTIGENS IN PATIENTS WITH ALCOHOLIC DELIRIUM COMPLICATED BY PNEUMONIA - Lukyanenko, T. V. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine")
The article presents the research results of the antistreptolysin O, antihyaluronidase, complement, and lysozyme levels in patients with alcoholic delirium complicated and not complicated by community-acquired pneumonia. Antistreptolysin O and antihyaluronidase levels in patients with pneumonia are above the norm and correlated with the severity of community-acquired pneumonia course. The complement and lysozyme titers are below the norm. We consider this to arise from the prolonged course of alcoholism, frequent bacterial complications caused by associations of mircroorganisms, including Streptococcus sp. The bacterial complications for this category of patients are caused by the microflora with a considerable level of antilysozyme and anticomplementary activity. The data we obtained may be used for prognosticating the infectious complications in patients with alcoholic delirium.